Chemical characterization, computational analysis and biological views on Daphne gnidioides Jaub. & Spach extracts: Can a new raw material be provided for biopharmaceutical applications?. (August 2020) - Can, Tevfik Hasan; Tufekci, Enis Fuat; Altunoglu, Yasemin Celik; Baloglu, Mehmet Cengiz; Llorent-Martínez, Eulogio J.; Stefanucci, Azzurra; Mollica, Adriano; Cichelli, Angelo; Zengin, Gokhan
Graphical abstract: Highlights: Plants are precious sources of bioactive compounds. Vicenin-2 and 3- O -p-coumaroyl-5- O -caffeoylquinic acid were the main identified compounds in leaf and both root and stem extracts, respectively. D. gnidioides had promising antibacterial and anticancer activities. D. gnidioides may have exhibited its anticancer effect against the HeLa cell line by increasing autophagic gene expression. The extracts of D. gnidioides exhibited significant tyrosinase inhibitory effects. Abstract: The scientific world tends to turn to natural products such as medicinal and aromatic plants because of the inadequacy of commercially available synthetic drugs as antibiotics or anticancer, and their adverse effects on healthy tissues. One of these plants is Daphne gnidioides Jaub. & Spach, which belongs to the Thymelaeaceae family, and there is no data in the literature on its biological activity. This study is aimed to elucidate the chemical profiles and in vitro anticancer, antibacterial and DNA protection and enzyme inhibitory properties of methanol extracts of root, stem, and leaf of D. gnidioides Jaub. & Spach. Polyphenolic components of the extracts were characterized by HPLC-MS/MS. The highest phenolic content was detected in the leaf extract (TIPC = 43.5 ± 0.5 mg/g DE), followed by stem (TIPC = 27.3 ± 0.7 mg/g DE) and root (TIPC = 18.3 ± 0.2 mg/g DE) extracts. Vicenin-2 and 3- O -p-coumaroyl-5- O -caffeoylquinic acid were the main identified compounds in leaf and both root and stem extracts, respectively. The extracts did not show any protective effect on DNA against experimental Fenton's reagent. The minimum inhibitory concentration and the minimum bactericidal concentration values for the root and leaf extracts against tested bacterial strains ranged from 31.25 to 500 μg/mL. After 48 h interaction of the cancer cell lines with the extracts, only the stem extract had significant cytotoxicity on HeLa cells (IC50 = 86.16 μg/mL). No remarkable activity of the extracts, which was tested against MDA-MB-231, was detected (IC50 > 1000 μg/mL). These data showed that D. gnidioides Jaub. & Spach stem extract inhibited the survival of HeLa cells in a time-dependent manner. After the treatment of IC50 concentration of stem extract with HeLa cells, an increase in LC3-II autophagic gene expression was detected. Also, the extracts exhibited significant tyrosinase inhibitory effects which were confirmed by molecular docking. To sum up, the tested extracts could be used as a starting point for the development of new multifunctional drugs.